Analysis of Farmers' Entrepreneurial Behavior, and its Effect on Farm Productivity - Ilham, Muh.; Karno, Edy; Halim, Muliha; Igo BD, Abdullah; Hasniah, Hasniah; Murniati, Murniati (Jurnal Economia, 2024)
AbstractThis study aims to analyze the entrepreneurial behavior of farmers from the aspect of formal education and farming experience and its influence on farm productivity. The research population was rice paddy farmers in Cialam Jaya Village, Konda Subdistrict, South Konawe District, Southeast Sulawesi Province totaling 215. The number of samples was 140 farmers who were determined proportionally based on the area of cultivated land with the Slovin method. This research is quantitative using path analysis to analyze the direct and indirect effects of exogenous variables on endogenous variables. The results showed that farmers' formal education and farming experience had a positive effect on entrepreneurial behavior. Formal education of farmers has no direct effect on farm productivity but influences entrepreneurial behavior. Farming experience has a direct effect on farm productivity and indirectly through entrepreneurial behavior. Entrepreneurial behavior has a positive effect on farm productivity. Keywords:Education, Experience, Entrepreneurial Behavior, Productivity